A Review on The Professional Development of Elementary Education Teachers in China - Ying Luo; Wenbin Xu (International Journal of Education and Learning, 2019)
The school field is the main field of teachers' study and work, which creates the field space for teachers' professional development. In order to explore the situation of teacher professional development in school field,based on the general condition of the research, from the research scope, the research perspective, the fit between "teaching" and "learning" in the study and the discussion that the theoretical research focuses on the value of practice, we have sorted out the hot spots and trends of the research on the professional development of Primary and high school teachers in China from the perspective of school standard.In the subsequent analysis, we need to make further thinking or exploration in the five aspects of the origin and fulcrum of the research, the positioning of the study, the establishment of the research thinking, the consideration of the influential factors in the research and the enlightenment of the research methodology.